The Al-Takâmul Baina Mafhum Al-Masyî’ah Wa Ta’lîm Al-Lughah Al-‘Arabiyah Fî Madrasah Mafâza Indonesia Al-Tsânawiyah (Ta’lîm Al-Qira’ah Namûdzajan) - Budi, Firmansah Setia; Ahmad, Nurwadjah; Suhartini, Andewi; Atha, Yusuf Ali Shaleh (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
This study aims to empower students linguistically and culturally. In the context of Arabic language education, it enables them to acquire some Islamic cultural knowledge related to doctrinal matters that are essential for any Muslim. The issue of divine will in creed has been widely discussed, and it is not appropriate to overlook it. This underscores the significant importance of integrating linguistic and doctrinal aspects. The study is based on field research, adopting a qualitative descriptive approach. Data is collected through observation and documentation. Following the study, the researchers conclude that achieving integration in Mufaza Indonesia Secondary School can be accomplished by formulating texts that convey information about the issue of divine will. This involves reviewing the prescribed textbooks for students in the school to ensure the absence of the desired topic. These texts can be presented to students in reading education, whether in intensive or extensive reading. To ensure students' understanding, teachers can pose objective questions about the text.